CYP3A5 and UGT1A9 Polymorphisms Influence Immunosuppressive Therapy in Pediatric Kidney Transplant Recipients - Krall, Paola; Yañez, Dominique; Rojo, Angélica; Delucchi, Ángela; Córdova, Miguel; Morales, Jorge; Boza, Pía; de la Rivera, Alonso; Espinoza, Natalie; Armijo, Natalia; Castañeda, Luis E.; Farfán, Mauricio J.; et al. (Frontiers in Pharmacology, 2021)
Background. Tacrolimus (TAC) and mycophenolic acid (MPA) are the main immunosuppressive drugs used in pediatric kidney transplantation. Single nucleotide polymorphisms (SNPs) in metabolizing enzymes and transporters might influence plasma levels of these drugs. Herein, we sought to determine the influence of SNPs on CYP3A5, MRP2 and UGT1A9 genes in Chilean pediatric kidney recipients using TAC and MPA. Patients and methods. A prospective study was performed on 104 pediatric kidney recipients that used TAC and MPA for immunosuppression. The median age at the time of transplantation was 8.1 years [Q1-Q3 4.5-11.6 yrs] and the main clinical diagnosis was a structural anomaly. In a subgroup of patients, a complete steroid withdrawal was made at Day7. The CYP3A5 polymorphism (ancestral allele *1; variant allele *3) was determined in the entire cohort, while MRP2 -24G>A, UGT1A9 -275T>A and UGT1A9 -2152C>T polymorphisms were determined in 53 patients. Genotypes were associated with trough drug concentrations (C0), dose requirements normalized by weight (TAC-D mg/kg) or body surface (MPA-D mg/m2), trough levels normalized by dose requirements (C0/D), and area under the curve in 12 hours normalized by dose requirements (AUC0-12h/D). Results. The frequencies of the variant alleles CYP3A5*3, MRP2-24A, UGT1A9-275A and UGT1A9-2152T were 76.9%, 22.1%, 6.6% and 2.9%, respectively. AUC0-12h/TAC-D were 1.6-fold higher in CYP3A5*3/*3 patients than in CYP3A5*1 carriers (CYP3A5*1/*3 and CYP3A5*1/*1). When analyzing patients with steroid withdrawal, CYP3A5*3/*3 patients had 1.7-fold higher AUC0-12h/TAC-D than the other genotypes. Patients carrying the CYP3A5*3/*3 genotype had higher TAC-C0, lower TAC-D and higher TAC-C0/D, consistently in a 6-month follow-up. Creatinine clearance was stable during the follow-up, regardless of the genotype. No significant differences between MRP2 and UGT1A9 genotypes were observed in MPA-C0, MPA-D or MPA-C0/D. However, patients carrying the UGT1A9-275A allele had lower AUC0-12h/MPA-D than those carrying the UGT1A9-275T ancestral allele. Conclusion. These results support that CYP3A5 and UGT1A9 genotyping in pediatric recipients might be useful and advisable to guide TAC and MPA dosing and monitoring in children that undergo kidney transplantation.